To the problem of the normative basis of migration in the Republic of Kazakhstan - Bozhkarauly, А. (KSU Publ., 2014)
The problem of migration is characterizing with special complexity, as it covers not only legal aspects, but also the problems of sociology, demograthy, political economy, ethnogeography, the problems of labor resources in the economics. The legal aspect have the special important place, because the migration is closely connected with the legal security, regulation and organization of migration processes, from which depends other problems of essential value for living conditions of the society.
Қазақстан Республикасындағы көші-қон нормативтік базасы туралы сұрақтар
К вопросу о нормативной базе миграции в Республике Казахстан
Keywords: Migration; types of migration; commuting; migration; labor migration; migration factors; ethnic migration; migration policy concept of migration